Opera 1986-1992. - Opera, Associazione culturale per le arti visive, Perugia (Perugia : Opera, Associazione culturale per le arti visive, 1992)
Mattiacci, Eliseo ; LeWitt, Sol ; Pisani, Vettor ; Dottori, Gerardo ; Bassiri, Bizhan ; Pistoletto, Michelangelo ; Calzolari, Pierpaolo ; Piersanti, Missomo ; Messina, Vittorio ; Spalletti, Ettore ; Licitra, Matteo ; Kounellis, Jannis ; Bagnoli, Marco ; Ranaldi, Renato ; Pagano, Giorgio ; Salvadori, Ettore ; etc.
Italiaans
boek